RABBANI CONCEPT OF EDUCATION IN THE QURAN SURAH ALI-IMRAN VERSE 79 AND VERSE 80 - Wilam Nafilah Robaeah; Rizal Rahmatullah; Muhamad Arif Nugraha; Oding Ahmad Effendy; Nofiem Taufiqul Akbar (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
One effort to build a strong Rabbani generation is through education. This research aims to discover the concept of Rabbani education in the Al-Quran surah ali-Imran verse 79 and verse 80. This research uses a library research method, namely a data collection technique that is not directly aimed at the research subject but through several book sources. Or articles, magazines, journals, and relevant sources. The results of this research are that the author states that Rabbani education in the Al-Quran surah ali-Imran verse 79 and verse 80 is an education that must be instilled from infancy through activities that contain religious elements in the family environment. This method can become a good habit for children in the future. So that you have a tough attitude and become a person who always draws closer to God Almighty